An unusual case of musculoskeletal graft-versus-host disease mimicking dermatomyopathies - Erdoğan, Bahattin; Özdemir, Zeynep Canan; Bör, Özcan; İlhan, Hüseyin (The Turkish Journal of Pediatrics, 2025)
Background. Musculoskeletal manifestations of graft-versus-host disease (GVHD) are rare but often result in mobility impairments, reducing the patient’s quality of life. Typically, such diagnoses are made based on clinical findings without the need for performing a muscle biopsy.Case Presentation. A 12-year-old boy diagnosed with acute myeloblastic leukemia (M2 subtype) underwent allogeneic hematopoietic stem cell transplantation (HSCT) due to a molecular relapse before his last chemotherapy cycle. Cyclosporine prophylaxis was stopped three months after transplantation, but the patient developed ocular, cutaneous, and oral chronic GVHD at four, five, and seven months after transplantation, respectively, for which intermittent steroid treatment and mycophenolate mofetil were given. All signs of GVHD resolved by one year after transplant, and immunosuppressive treatment was stopped; however, three months later, he experienced muscular weakness in bilateral upper and lower extremities. Subsequently, immunosuppressive treatment was restarted following a muscle biopsy.Conclusion. Diagnosing musculoskeletal GVHD is challenging due to the lack of reliable parameters for histopathological diagnosis, and initial clinical findings can be mistaken for steroid-induced myopathy or inflammatory dermatomyopathies. We applied methylprednisolone, mycophenolate mofetil and extracorporeal photopheresis for treatment, and the clinical findings completely improved with these treatments.
Keywords: graft-versus-host disease; allogeneic bone marrow transplantation; musculoskeletal symptoms; inflammatory dermatomyopathy